2021
DOI: 10.21037/gs-21-405
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough in breast reconstruction in the context of COVID-19: safety and efficiency of endoscopic breast reconstruction at a day surgery center

Abstract: Background: In recently years, breast endoscopic reconstruction surgery is becoming increasingly popular.And we have explored a series of endoscopic breast reconstruction procedures and applied it to our day surgery under the epidemic control of the novel coronavirus.Methods: The present study was a retrospective analysis. Patients who underwent unilateral breast endoscopic reconstruction surgery in the West China Hospital from April 2017 to February 2021 were included in the study. Patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The surgical technique for NSM and the concept of the “HUAXI hole 1” has been described previously ( 20 , 21 ). The retro-areolar tissue should be carefully dissected by surgical scissors to protect the blood supply and prevent nipple ischemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical technique for NSM and the concept of the “HUAXI hole 1” has been described previously ( 20 , 21 ). The retro-areolar tissue should be carefully dissected by surgical scissors to protect the blood supply and prevent nipple ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…Next, NSM was performed in the order of the subpectoral space (if an implant was placed in the subpectoral position, by a coagulation hook), retromammary space (by a coagulation hook with the assistance of forceps), and the subcutaneous layer of breast, which was dissected using the PMOD to retro-areolar tissue under direct vision, and the rest of the layer was then performed using the PMOD inserted through the "HUAXI hole 1" (located next to the areola in the upper-outer quadrant) (see Figure 2C). The surgical technique for NSM and the concept of the "HUAXI hole 1" has been described previously (20,21). The retro-areolar tissue should be carefully dissected by surgical scissors to protect the blood supply and prevent nipple ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic was administered using a total intravenous anesthesia protocol or intravenous and inhalational combined anesthesia. The surgery process of total subpectoral breast reconstruction can be obtained in our other studies [21,22] . As we continue to evolve surgical techniques, we found that pre-pectoral implant placement can shorten the operation time, reduce postoperative pain and improve breast satisfaction of patients compared to subpectoral technique.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The progress of technology (especially the applications of robot/endoscopy nipple/skin-sparing mastectomy(R/E-N/SSM), three dimensional videoscope) greatly reduces the trauma and complications associated with breast reconstruction [17][18][19][20] , however, existing studies on day surgery of breast reconstruction predominantly focus on conventional, open breast reconstruction. West China Hospital pioneered E-N/SSM with breast reconstruction using the original endoscopic technique with reversed dissection order, "HUAXI Hole 1" and "pulling threads method of mesh" in the day surgery department, which can significantly improve the aesthetic of breast, shorten the operation time and minimize the resources [21] . However there were small number patients in our prior study [21] , here we aim to report the preliminary results, complications and patient-reported outcome from preliminary 68 procedures of single-axillary-incision E-N/SSM with immediate IBBR of day surgery to assess its safety and effectiveness convincingly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation